Relationship of climate change variables and nutritional status of preschool children of farming households - Talavera, Maria Theresa M. (2015.)
Climate change and malnutrition are two phenomenon that are affecting millions of people globally. It is caused by natural and anthopogenic activities. It affects children and poor households. There is a need to prepare families and children to adapt to the impacts of climate change since it will affect health and food and nutrition security. However, there are very few studies that examined the relationship of climate change variables and nutritional status of preschool children. The results is hoped to contribute to the information on climate change and its impact on nutrition. This is a cross-sectional study design that includes 198 households from Los Banos, Laguna and Infanta, Quezon. Los Banos has a wet and dry season characteristics of climate type 1 while Infanta is wet throughout the year which is inherent to areas with climate type 2. Anthropometric measurements and climate change variables such as temperature and rainfall were collected for 6 months. Data on climate change were obtained from PAGASA. Questionnaires for mothers and fathers were pretested and the final versions were used to collect data on socio-economic-demographic, feeding practices, health status, and hygiene and sanitation. The main findings are as follows: 1) climate change is occurring in Los Banos and Infanta; 2) there were more stunted and underweight children in Los Banos than Infanta; 3) rainfall and temperature were found to be associated with children's health status in Los Banos and Infanta; 4) rainfall and temperature were associated with Infanta mothers' monthly income only (p=0.048); 5) there is a positive and significant association between energy (p=0.079) and vitamin A (p=0.099) intake of Infanta children and rainfall; 6) rainfall and temperature were correlated with the health status Los Banos and Infanta children; and 7) rainfall was positively and significantly correlated with underweight children of Los Banos (p=0.005) but not stunting. In Infanta, however, no climate variables were found to be associated with the children's nutritional status. In addition to climate variables, other factors found to be associated with stunting were mother's age, father's age, father's monthly income, intake of energy, iron, and vitamin A, feeding practices, sanitation and hygiene practices, access to health care, and health status. Thefactors found to be associated with underweight children were mother's employment status, intake of energy, iron and vitamin A, and sanitation and hygiene practices, family size and mother's primary occupation and health status. Area and rainfall can predict underweight in children. In addition, results of the regression modeling showed that rainfall is one of the predictive variables for stunting and that location plays a role in the development of malnutrition. In conclusion, climate change variables can partially explain the development of malnutrition among children. There are other non-climate change variables that remain to cause malnutrition. Because of the nature of climate change which is slow and gradual onset, the impact is hardly felt unless extreme events such as typhoons occur. The location determines the type of climate the children and households are exposed and related risks which are place or location specific, making an area more at risk than other areas.
Available in CD, pdf copy.
Thesis (DrPh, Nutrition)--University of the Philippines Manila.
Keywords: Nutrition -- Evaluation; Malnutrition; Climatic changes